impelementation IMPLEMENTATION OF STUDENT CHARACTER EDUCATION THROUGH MODELING HABITUAL BEHAVIOR IN CULTURAL ARTS LEARNING IN GRADE IV SDN GANDEKAN SURAKKARTA IN 2022/2023 ACADEMIC YEAR: ENGLISH - Dzari Wahyu; Oktiana Handini; sarafuddin sarafuddin (Widya Wacana: Jurnal Ilmiah, 2023)
This study aimed to determine the implementation of stundent character education through modeling and habitual behavior in cultural arts learning in class 4 SDN Gandekan in 2022/2023 academic year. This type of research was qualitative research which described attitutudes, perceptions, scientific behavior taken based on structured data. Data collection techniques used were interviews, questionnaires, documentation, and observation, sources of data obtained were through school principal, teachers in class 4, students in class 4. Supporting sources were obtained through the Merdeka curicculum, student profiles of Pancasila, and assessment planning at school. The research object was the implementation of character education about modeling and habitual behavior in learning arts and culture in class 4. The supporting factor in this research was the openness of attitude in the research process which provided complete and factual data. Character education about the profile of Pancasila students in a goal in education at SDN Gandekan Surakarta which is reflected in the school’s vision and mission. Broadly the formation of student character is implemented through teaching and learning activities every day, especially in learning arts and culture. In this case, learning places more emphasis on modeling and habitual behavior of students so that they are always used to being good role models in their environment. Keywords: Character education, Implementation of Character Education, Modeling, Habitual Behavior, Cultural Arts